Lankesteriana, a new genus in the pleurothallidinae (orchidaceae) - Karremans, Adam P (Universidad de Costa Rica, 2014)
We estimated phylogenetic relationships within Anathallis and related genera using Bayesian analyses of nrITS sequence data. The genus is biphyletic in the molecular trees. A novel generic concept, Lankesteriana, is proposed for the species Anathallis barbulata and 19 close relatives. The genus is more closely related to some species of Trichosalpinx and Zootrophion than to Anathallis s.s. Species previously transferred from Pleurothallis subgen. Acuminatia sect. Acuminatae to Anathallis, are here transferred to Stelis, to which they are related phylogenetically. A few additional transfers to Anathallis are made. Lankesteriana is described and characterized, and the necessary taxonomic transfers are made